KELOMPOK SADAR WISATA (POKDARWIS) DESA SAWENTAR SEBAGAI PENGHELA PELESTARIAN BAHASA DAN BUDAYA JAWA - Adi Chandra, Afry (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
As the developments of the times , movement culture preservation done in a way that have variation. Group Aware of Tourism ( Pokdarwis ) Sawentar’s village being one of drags conservation movement for culture or language , especially Java . Research qualitative descriptive aims to understand the conservation of language and culture Javanese which carried out by the Pokdarwis in the area around cultural site (Sawentar Temple). The research results show that the conservation of their language and culture Java done by Pokdarwis Sawentar’s village covering, the jaranan arts, learning batik activity, tourist visit,and cultural class of Lawang Wentar.